2016
DOI: 10.1515/rjim-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Hypothyroidism in a Population-Based Study of Iranian Women

Abstract: Background. Recent biochemical and physiological investigations have focused on the fundament of mood disorders in thyroid dysfunction. The present study aimed to address depressive disorder in a sample of Iranian hypothyroid women compared to euthyroid individuals.Methods. Thirty consecutive hypothyroid female patients aged 25 to 40 years who referred to the Endocrinology and Metabolism Clinic at Rasoul-e-Akram Hospital in Tehran within a four-month period in 2015 were assessed. Thirty healthy euthyroid subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Women with underlying diseases, such as diabetes, high blood pressure, and thyroiditis, had a rate of performing breast self-examinations that were 29% lower than women who had no underlying diseases. Different studies have shown that the prevalence of depression and mood disorders was high in women with diabetes, high blood pressure, hypothyroidism, and hyperthyroidism [26], [27], [28], [29]. Given that depression and mood disorders are considered barriers to self-care behaviours [30], the results of this study were noticeable, and the rate of performing breast self-examination for women with a history of underlying diseases was lower than the rate for healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…Women with underlying diseases, such as diabetes, high blood pressure, and thyroiditis, had a rate of performing breast self-examinations that were 29% lower than women who had no underlying diseases. Different studies have shown that the prevalence of depression and mood disorders was high in women with diabetes, high blood pressure, hypothyroidism, and hyperthyroidism [26], [27], [28], [29]. Given that depression and mood disorders are considered barriers to self-care behaviours [30], the results of this study were noticeable, and the rate of performing breast self-examination for women with a history of underlying diseases was lower than the rate for healthy women.…”
Section: Discussionmentioning
confidence: 99%
“…] These manifestations may be severe, [18,19] and may exceptionally reveal the disease. [10,18] Depression remains rare, complicating only 4% of overt hypothyroidism [20] and is often characterized by its severity and its resistance to antidepressant therapy. [21,22] Indeed, the multicenter European study of resistant depression (GSRD Study) performed on 1410 patients, showed that 13% of subjects with a major depressive syndrome had underlying hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…[21] This depression appears to be more common in elderly subjects, particularly women, and it has been shown that hypothyroid women are significantly predisposed to the development of depressive syndrome regardless of their basic demographic and socio-economic characteristics. [20] The particular frequency of depression during hypothyroidism suggests common mechanisms to the point that several authors present the hypothesis of "brain hypothyroidism" to explain the pathogenesis of depression during this endocrinopathy. [13] This theory is based on the effects of deprivation in thyroid hormones on brain tissue, and on the direct effects of thyroid pathology, especially autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] An Indian case–control study done in Mumbai 2017 studied the relationship between depression and hypothyroidism and concluded that inflammatory cytokines are associated with depression that can be relieved by treating autoimmune hypothyroidism, so they recommended that all patients with depression should be screened for hypothyroidism. [21] Two cross-sectional studies conducted in India (2016–2017) to estimate the prevalence of depression among hypothyroid patients on 100 and 144 patients showed that about 60% and 12.5% of hypothyroid patients had depression, respectively.…”
Section: Introductionmentioning
confidence: 99%